Catholic demonolgy in the contemporary tijes : challenges and prospects - Garibay, Bryan H. (Immaculate Conception School of Theology : [s.n.], 2019)
One of the first tenets of the Creed is God the Father's creation "of heaven and earth, of all things visible and invisible" Explicitly mentioned here is the creation of "invisible" reality, which our physical senses cannot perceive Christian faith believes this to be the spiritual world, where God is, and so are other spiritual realities, like the angels and demons. This segment of the Christian faith was once a very rich theme for academic inquiry and pastoral and moral instruction. However, at the dawn of the modern era's rationalization, and the postmodern era's openness, this topic about the supernatural and spiritual seemed to be misunderstood, marginalized and ignored, even within theological circles. On one hand, angels, demons, and any supernatural being (except for God Himself) were regarded as unnecessary and outdated, if not blatantly wrong. On the other hand, an unhealthy obsession on the topic can lead to superstitious beliefs, which are far from, if not opposed to, the authentic teachings of the Church. The Church as Mater et Magistra is mandated by her prophetic and sanctifying mission to proclaim the truth about this matter which is slowly resurfacing and breeding confusion in the contemporary times. This study is a humble contribution to the need for a primer on systematic and theologically sound presentation of Catholic Demonology in its richness. It attempts to present the Catholic Demonology as grounded in Sacred Scriptures. Magisterium, and other theological sources. It then surveys the contemporary challenging views about the topic of demons and their activities, as seen in various lenses. Finally, it seeks to discover the place of Demonology in the contemporary Christian Faith, and propose some areas by which it can be appreciated properly in lieu of the Church's New Evangelization.
Bibliography: pages 1116-122.
CHED-La Union
Keywords: Demonology